Determination of Optimal Number of Clusters in Cure Using Representative Points - Robindro, Khumukcham; Khumukcham, Bisheshwar; Nilakanta Singh, Ksh (International Journal of Computer Sciences and Engineering, 2025)
In most of the clustering algorithms, the number of clusters has to be supplied in as an input. In CURE clustering algorithm also, the same problem exists. In this paper, we try to find the optimal cluster number in the CURE clustering algorithm by calculating an optimality measure corresponding to each cluster number produced by CURE clustering algorithm after it enters a range ,based on the intra cluster measure and the inter cluster measure of the clusters. The clustering along with the optimality check continues as long the optimality measure is increasing and the cluster number doesn’t fall below the minimum boundary of our range.